2015 IEEE Sensors Applications Symposium (SAS) 2015
DOI: 10.1109/sas.2015.7133594
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evaluation of OI-MAC: Direct interconnection between wireless sensor networks for collaborative monitoring

Abstract: Abstract-Cooperation between co-located Wireless Sensor Networks (WSNs) has the potential to present new opportunities for novel applications and provide network performance improvements. The traditional interconnection approach for WSNs is based on a backbone network such as the Internet, but this may have intermittent or unavailable connectivity in remote locations. To address this, Opportunistic Direct Interconnection (ODI) has been proposed to allow distinct and independent WSNs to communicate directly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In [7], the framework from ODI was updated to consider the heterogeneity of MAC protocols. While our previous work has validated OI-MAC experimentally [8].This new vision for heterogeneous ODI has only been evaluated through simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], the framework from ODI was updated to consider the heterogeneity of MAC protocols. While our previous work has validated OI-MAC experimentally [8].This new vision for heterogeneous ODI has only been evaluated through simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [5]- [7] showed benets of node collaboration in multidomain WSNs under practical implementation. The results showed that cooperation with co-located sensor devices in dierent networks can increase the network lifetime.…”
mentioning
confidence: 99%